Przestępna nieumyślność jako błąd zawiniony (analiza psychologiczna): [Unintentional criminal acts as faulty error. Psychological analysis] (Studia Prawnicze / The Legal Studies, 2023)
While discussing the problem of unintentional guilt from psychological point of view it seems most important to find out why the attention of a perpetrator was not concentrated on values protected by the law, which in results caused the damages of such values. The lack of such attention results from the fact that a perpetrator does not consider a given value sufficiently meaningful. Depending upon the importance of a given value to the perpetrator in a given situation he behaves in a manner convenient to him, accepting or not accepting certain values in a given moment. As a result, a crime — also unintentional one — may be committed, if the perpetrator concentrates his attention on particular values important to him but ignores (even unconsiously) values protected by penal law. All this means that in psychological sense it is possible to analyse the guilt also in relation to unintentional guilt (even in the form of negligence). Thanks to such analysis it is possible to look at the whole problem of guilt (intentional and unintentional) in a more uniform way, taking in account all the consequences (in the sphere of legal grounds of penal responsibility, legislative policy and penal policy).